Fully Transparent Nanocomposite Coating with an Amorphous Alumina Matrix and Exceptional Wear and Scratch Resistance. (29th April 2016) - Valant, Matjaz; Luin, Uroš; Fanetti, Mattia; Mavrič, Andraž; Vyshniakova, Kateryna; Siketić, Zdravko; Kalin, Mitjan
Abstract : This study presents a method for high temperature stabilization of amorphous alumina. The strain‐induced stabilization is obtained by dispersion of rigid globular polycarbosilane macromolecules within an alumina matrix. The alumina matrix remains amorphous even at 1200 °C. This study confirms the chemical composition of the coating with an advanced chemical depth‐profile analysis and shows its nanostructure by transmission electron microscopy. Based on this amorphous nanocomposite, a new facile and inexpensive coating for mechanical protection of glass surfaces is further developed. The nanocomposite coating is characterized by a full optical transparency and exceptional tribological characteristics. The wear resistance exceeds that of the current advanced ion‐exchanged boroaluminosilicate glass by a factor of 25–35 whereas its scratch resistance is exceeded by more than an order of magnitude. Abstract : The strain‐induced high‐temperature stabilization of amorphous alumina is obtained by dispersion of rigid globular polycarbosilane macromolecules within the alumina matrix. This nanocomposite is a base for a new facile and inexpensive coating for mechanical protection of glass surfaces. The nanocomposite coating is characterized by a full optical transparency and exceptional tribological characteristics.